2010
DOI: 10.1002/pbc.22606
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical cardiac dysfunction and exercise performance in childhood cancer survivors

Abstract: Our results confirm that even patients treated with a median anthracycline dose of 240 mg/m(2) (range 100-490) are at considerable risk of exhibiting subclinical cardiac dysfunction that, however, does not seem to alter the physiologic response of the cardiovascular system to dynamic exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 30 publications
4
34
0
1
Order By: Relevance
“…One recent study showed that despite subclinical cardiac dysfunction, children treated with anthracyclines (median dose, 240 mg/m 2 ) had normal physiological responses to exercise. 622 Studies on the effects of cancer and cancer treatment on daily physical activity have had inconsistent results. 171,608 Some report normal activities, and others report decreased physical activity after cancer diagnosis that persists for years and that children who were generally inactive before cancer treatment tend to remain so after treatment.…”
Section: Exercise Capacity and Physical Activity Interventionsmentioning
confidence: 99%
“…One recent study showed that despite subclinical cardiac dysfunction, children treated with anthracyclines (median dose, 240 mg/m 2 ) had normal physiological responses to exercise. 622 Studies on the effects of cancer and cancer treatment on daily physical activity have had inconsistent results. 171,608 Some report normal activities, and others report decreased physical activity after cancer diagnosis that persists for years and that children who were generally inactive before cancer treatment tend to remain so after treatment.…”
Section: Exercise Capacity and Physical Activity Interventionsmentioning
confidence: 99%
“…Among childhood cancer survivors exposed to anthracyclines, younger than 18 years old, and at least 1 year post-treatment, De Caro et al found that CRF was significantly lower in survivors compared with controls (VO 2max : 41.4 -7.7 mL/kg/min vs. 45.7 -4.3 mL/kg/min, p = 0.05), respectively. 22 Conversely, in a separate study of childhood cancer survivors younger than 21 years old, De Caro et al found that only male survivors younger than 13 years of age had reduced CRF compared with age-and sex-matched controls. 23 Miller et al assessed CRF among childhood cancer survivors at least 4 years post-diagnosis with a median followup time of 13.4 years.…”
Section: Crf In Childhood Cancer Survivorsmentioning
confidence: 92%
“…(32,35) One study, however, did note a smaller rise in peak E and fall in E/A ratio during dobutamine administration after anthracycline therapy and concluded that these findings represent the unmasking of early stage anthracycline cardiotoxicity. (36) Evaluation of contractile reserve by stress testing has also been investigated, specifically in a paediatric population.…”
Section: Contractile Reservementioning
confidence: 99%
“…(39) More recently, it was shown that survivors of childhood cancer had lower percent thickening at end systole and reduced end-systolic wall stress after exercise compared to healthy controls. (35) At this time, however, a role for stress echocardiography in the routine clinical evaluation of patients treated with anthracyclines has not been defined.…”
Section: Contractile Reservementioning
confidence: 99%
See 1 more Smart Citation